A new species of Eupithecia Curtis (Lepidoptera, Geometridae) from the Azapa Valley, northern Chile - Héctor A. Vargas (Revista Brasileira de Entomologia, 2011)
A new species of Eupithecia Curtis (Lepidoptera, Geometridae) from the Azapa Valley, northern Chile. Male and female adults of a new species of Eupithecia Curtis from the Arica Province, Chile are described and illustrated. The species is compared with E. yubitzae Vargas & Parra, 2004, from the same locality, and E. galapagosata Landry & Rindge 1995, from the Galapagos Islands, Ecuador.